2006
DOI: 10.1164/rccm.200512-1930oc
|View full text |Cite
|
Sign up to set email alerts
|

Relative Corticosteroid Insensitivity of Peripheral Blood Mononuclear Cells in Severe Asthma

Abstract: Rationale and Objectives: Patients with severe asthma have a poor therapeutic response to corticosteroid therapy, and corticosteroid responsiveness cannot be easily measured in these patients. We hypothesized that this poor response is associated with a reduced effect of corticosteroids to inhibit cytokine release from activated peripheral blood mononuclear cells (PBMCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(161 citation statements)
references
References 26 publications
12
146
2
1
Order By: Relevance
“…It can be demonstrated in peripheral blood mononuclear cells and alveolar macrophages, and in resident cells such as airway smooth muscle cells from patients with severe asthma [166][167][168][169], but the relationship of these in vitro studies to in vivo responses is not well understood. Corticosteroid insensitivity has been associated with different comorbid conditions such as obesity [170], smoking [171], low vitamin D levels [172,173], and non-eosinophilic (low-Th2 inflammation) mainly in adults [174].…”
Section: Using Established Asthma Medications Corticosteroid Insensitmentioning
confidence: 99%
“…It can be demonstrated in peripheral blood mononuclear cells and alveolar macrophages, and in resident cells such as airway smooth muscle cells from patients with severe asthma [166][167][168][169], but the relationship of these in vitro studies to in vivo responses is not well understood. Corticosteroid insensitivity has been associated with different comorbid conditions such as obesity [170], smoking [171], low vitamin D levels [172,173], and non-eosinophilic (low-Th2 inflammation) mainly in adults [174].…”
Section: Using Established Asthma Medications Corticosteroid Insensitmentioning
confidence: 99%
“…Intact HDAC2 function is indispensable in mediating the transrepression action of steroids to modulate transcriptional activity of NF-kB and AP-1 (22). Elevated HAT activity and impaired HDAC2 protein expression and activity have been reported in lung tissues, alveolar macrophages, and PBMCs from COPD and severe asthma patients (29,44,45). In the present study, we observed a major drop in nuclear HDAC2 level and total HDAC activity and an increase of the total HAT/HDAC activity ratio upon LPS/IFN-g stimulation, which might be responsible for LPS/IFN-g-induced steroid insensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…There is altered expression of markers of epithelial proliferation such as an increased expression of the proliferation marker, Ki67, and reduced expression of Bcl-2, a negative regulator of epithelial cell death [82]. Studies in alveolar macrophages and blood mononuclear cells from patients with severe asthma confirmed the presence of CS insensitivity, associated with an increase in p38 MAPK activity [11,83].…”
Section: Corticosteroid Insensitivity In Airways Diseasementioning
confidence: 96%